Lexical Dimensions Within the Register of Scientific Prose Style - Khamesian, Minoo (Cultural and religious studies, 2017)
Words, as we know, cannot be torn apart either from the concepts they express or from the functions they perform in each communicative context. In this regard, the unity of words and concepts is considered an indispensible part of all communication. Being a great hindrance on the way to efficient scientific communication, competence in general academic vocabulary seems to be of paramount importance. The reflection of the process of scientific work can be found in the general scientific vocabulary in order to establish a convenient, rational and simple system in this register. The present work focused on the lexical dimensions of scientific discourse in the hope to illuminate the path to bring about a better understanding of one of the crucial aspects of this register which seems to be overlooked while teaching EAP to non-native learners, a pragmatically oriented system which might provide a scientifically controlled "tool", to non-native learners.